2015
DOI: 10.1074/jbc.m115.640656
|View full text |Cite
|
Sign up to set email alerts
|

Ion Transporter NKCC1, Modulator of Neurogenesis in Murine Olfactory Neurons

Abstract: Background: NKCC1 is controversially discussed as the main chloride transporter in olfactory epithelium. Results: Lack of NKCC1 results in impaired odorant detection and a decrease in the number of mature neurons. Conclusion: NKCC1 is involved in chloride accumulation but also reveals an impact in neurogenesis. Significance: This work contributes to the understanding of olfactory epithelium neurogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…AE2 and/or other HCO 3 - dependent mechanisms contribute to Cl - regulation, and thus could be compensating for the loss of NKCC1 in GnRH neurons. Consistent with this hypothesis, Haering et al recently reported increases in transcript for three Cl - transporters including AE2 (Slc4a2), in the olfactory epithelium of NKCC1 -/- mice [ 41 ].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…AE2 and/or other HCO 3 - dependent mechanisms contribute to Cl - regulation, and thus could be compensating for the loss of NKCC1 in GnRH neurons. Consistent with this hypothesis, Haering et al recently reported increases in transcript for three Cl - transporters including AE2 (Slc4a2), in the olfactory epithelium of NKCC1 -/- mice [ 41 ].…”
Section: Discussionmentioning
confidence: 84%
“…Previous research has shown that tissue from NKCC1 -/- mice show compensatory changes for the loss of NKCC1 [ 40 , 41 ]. Therefore we measured the MUS response in NIH Swiss WT mice (“WT”), either with or without the NKCC1 inhibitor Bumetanide (BUME).…”
Section: Resultsmentioning
confidence: 99%
“…These might be caused by the reduction of cell number, and thickness of the neuronal layer in the MOE of AC3 −/− mice as revealed in many olfactory related gene knockout mice. For example, a decrease of 20% was revealed in both thickness and cell number in the MOE of NKCC1-deficient mice [ 46 ]. In the ATF5 knockout (KO) MOEs, the numbers of OR-expressing neurons are significantly reduced [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A mixture of 89 molecules was Mixture C (Henkel 100 #13‐11,845; n = 100) containing odorants of different classes and groups, including aromatics, aliphatics, alcohols, aldehydes, esters, ethers, ketones, amines, alkanes, heterocyclics, etc. This mixture of odorants and subdivisions of a smaller number of components have been previously used in studies examining the specificity and sensitivity of human ORs (Wetzel et al, ) and olfactory epithelium signaling (Haering et al, ; Wetzel, Brunert, & Hatt, ). In the current study, we expanded the perspective on Henkel100 by looking at its olfactory thresholds.…”
Section: Methodsmentioning
confidence: 99%